Workshop Pengembangan Bahan Ajar Berbasis Proyek Bagi Guru Sekolah Dasar di Pulau-Pulau Kecil Perbatasan - Theophanie Pattinasarany; Karten Halirat; Lowisye Leatomu; Mukh Khusnaini (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Education plays an important role in the development of a nation, with the quality of education being the responsibility of all parties, especially teachers. In Elementary Schools (SD), teachers must utilize various open materials in learning to motivate students, help them explore basic abilities, and guide them to discover their potential. Teaching materials in learning, such as developing teaching materials using a project-based approach that has great potential to integrate local values ​​and utilize the potential of the surrounding environment, so that learning becomes more meaningful for students. In SD Negeri 8 Dobo, it was found that many teachers were not yet skilled in creating open materials in learning and the learning process was still teacher-themed. To overcome this, community service activities were carried out by creating a Workshop on Developing Teaching Materials Based on Projects for Elementary School Teachers in Small Islands. This workshop aims to improve teacher competence, especially in small border island areas, in developing project-based teaching materials. Teachers will be trained to design learning projects that are interesting, challenging, and relevant to the local context, and support their implementation with appropriate open materials. The expected end results include improving teachers' pedagogical skills, the formation of collaborative networks between teachers, and the creation of learning project plans that can be implemented in their respective schools. In addition, this activity will also provide practical strategies to overcome the geographical and social challenges facing teachers in border areas. Thus, this workshop is expected to be a strategic step in improving the quality of education in the region.